Empowering Women in Leadership: Exploring Public Relations in Malaysia Madani Context - Yamunah Mohan; Nur Kareelawati Abd. Karim (Faculty of Leadership & Management, 2024)
E-Proceeding of 4th International Conference on Islam, Media and Communication (ICIMac 2024): “Communication & Digitisation in Madani Society”/ Muhammad Raqib Mohd Sofian, , Siti Suriani Othman, Safiyyah Sabri, Osama Kanaker & Ihab Ahmed Ra’uf Awais. 5th March 2024 Organized by : Faculty of Leadership & Management